Thermal and morphological properties of polyhydroxyalkanoate / nanosilver composite - Kandasamy, S.; Suriati, Ghazali; Saidatul Shima, Jamari (Penerbit Universiti Malaysia Pahang, 2023)
Conventional plastic can lead to endless pollution as it took millions of years to be disposed of, hence an alternative to using biodegradable plastic replacing regular everyday plastic has highly participated. Polyhydroxyalkanoates (PHA) have the characteristics of a biodegradable plastic however, it exhibits low heat distortion temperature. The objective of this research is to investigate the effect of nanosilver additions on the thermal properties of the PHA composite and its morphology behavior. Initially,4 wt/v of PHA was dissolved into 30mL dichloromethane at room temperature. After that, the nanosilver particle was added with 10mL dichloromethane and it was ultrasonicated at 10 minutes. Ultrasonicated nanosilver in dichloromethane mixture was mixed with PHA in dichloromethane for 20 minutes using a magnetic stirrer. Then, thin polymeric films with a thickness of 10 µm were obtained by the solution casting method. The obtained films were then carefully dried at room temperature for 24 hours. These steps were repeated with the addition of 0.25 wt% and 0.5wt% nanosilver suspension in dichloromethane to PHA solution. The thermal properties and morphology analysis of PHA/nanosilver composite will be investigated using thermal gravimetric analysis(TGA) and field emission scanning electron microscopy (FESEM). Based on thermal properties, PHA/0.5wt% nanosilver has shown a lower onset temperature compared to the pure PHA. This indicates that PHA/0.5wt% nanosilver has a slower degradation rate and higher thermal stability. In conclusion, nanosilver has greatly improved PHA properties into promising biodegradable plastics.